Moisture-driven carbonation kinetics for ultrafast CO 2 mineralization - Yining Gao; Yong Tao; Gen Li; Peiliang Shen; Roland J.-M. Pellenq; Chi Sun Poon (Proceedings of the National Academy of Sciences, 2025)
CO 2 mineralization, a process where CO 2 reacts with minerals to form stable carbonates, presents a sustainable approach for CO 2 sequestration and mitigation of global warming. While the crucial role of water in regulating CO 2 mineralization efficiency is widely acknowledged, a comprehensive understanding of the underlying mechanisms remains elusive. This study employs a combined experimental and atomistic simulation approach to elucidate the intricate mechanisms governing moisture-driven carbonation kinetics of calcium-bearing minerals. A self-designed carbonation reactor equipped with an ultrasonic atomizer is used to meticulously control the water content during carbonation experiments. Grand Canonical Monte Carlo simulations reveal that maximum CO 2 uptake occurs at a critical water content where the initiation of capillary condensation significantly enhanced liquid–gas interactions. This phenomenon leads to CO 2 adsorption–driven ultrafast carbonation at an optimal moisture content (0.1 to 0.2 g/g, water mass ratio to total wet mass of the mineral). A higher moisture content decimates the carbonation rate by crippling CO 2 intake within mineral pores. However, at exceptionally high moisture levels, the carbonation reaction sites shift from internal mesopores to the grain surface. This results in surface dissolution–driven ultrafast carbonation, attributed to the monotonically decreasing free energy of dissolution with increasing surface water thickness, as revealed by metadynamics simulations. This study provides a fundamental and unified understanding of the multifaceted role of water in mineral carbonation, paving the way for optimizing ultrafast CO 2 mineralization strategies for global decarbonization efforts.